Higher education for the sustainable development goals bridging the Global North and South - Caporarello, Leonardo; Kumar, Payal; Agrawal, Anirudh (Emerald Publishing, 2024)
The Global North and Global South are in different stages of the journeys towards a sustainable future. The Global North is focusing on cutting carbon emissions and discussing "de-growth", whilst large parts of the Global South are still struggling to move out of poverty, increasing their carbon emissions in many places. This division must be addressed through education, understanding the division and providing possible solutions. Higher Education Institutions (HEI) should take on a leadership role in shaping young minds through education and research to foster an enhanced perception of the variances in sustainability approaches of the Global North and Global South. Presenting chapters from an international set of contributors, this collection provides practical insights that inform practice, focusing on two themes: the design of HEI curricula; and a specific focus on Global North and Global South divide in addressing social and political differences, and the role that HEIs can play in addressing the divide. Higher Education for the Sustainable Development Goals is a must read for policymakers and researchers, learners, and management teams at HEIs.
Includes index. - Includes bibliographical references. - Print version record
Keywords: Education, Higher; Economic development / Effect of education on; Sustainable development; Business & Economics; Development; Sustainable Development; Development economics & emerging economies